PENGEMBANGAN SISTEM ADMINISTRASI SURAT MENYURAT PADA KANTOR BUPATI KUPANG - Pauldynov Marthin Djuma; Skolastika S. Igon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Correspondence administration at the Office of the Regent of Kupang is a critical process for recording, distributing, archiving, and monitoring official letters. The existing conventional process caused delays in letter distribution, difficulty in archive retrieval, and limited visibility of letter status. This study aimed to develop a web-based correspondence administration system called SIPDA to support structured and traceable letter management. The research used the Waterfall model consisting of requirements analysis, system design, implementation, testing, and maintenance planning. Data were collected through observation, interviews, and documentation studies at the General Affairs section of the Office of the Regent of Kupang. The system was designed with role-based access for Admin, Employee, and Leader users, while leader access was mapped to official positions to maintain continuity of letter disposition. The implementation produced core features for incoming letter management, outgoing letter archiving, letter agenda, disposition, tracking, user management, and WhatsApp notification support. Functional and black-box testing showed that the main features operated according to the expected outputs. The results indicate that SIPDA can improve documentation, support monitoring of letter movement, and increase transparency in the disposition flow.